The Influence of Organizational Culture and Work Motivation on Employee Performance at The Alfamidi Office in Ambon City - Asiani Sijabat (Sean Institute, 2026)
This study aims to analyze the influence of organizational culture and work motivation on employee performance at the Alfamidi office in Ambon City. The study used a quantitative approach with a survey method of 42 respondents, who were Alfamidi employees in Ambon City. Data collection was carried out by distributing questionnaires using a five-point Likert scale. Data analysis used multiple linear regression with the help of SPSS. The results of the study indicate that organizational culture and work motivation have a positive and significant influence on employee performance. Partial test results indicate that organizational culture significantly influences employee performance. Simultaneous test results indicate that organizational culture and work motivation simultaneously have a significant influence on employee performance. These findings indicate that companies need to strengthen organizational culture and increase work motivation to sustainably improve employee productivity and work quality.